2007
DOI: 10.1086/511134
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in CUL4B, Which Encodes a Ubiquitin E3 Ligase Subunit, Cause an X-linked Mental Retardation Syndrome Associated with Aggressive Outbursts, Seizures, Relative Macrocephaly, Central Obesity, Hypogonadism, Pes Cavus, and Tremor

Abstract: We have identified three truncating, two splice-site, and three missense variants at conserved amino acids in the CUL4B gene on Xq24 in 8 of 250 families with X-linked mental retardation (XLMR). During affected subjects' adolescence, a syndrome emerged with delayed puberty, hypogonadism, relative macrocephaly, moderate short stature, central obesity, unprovoked aggressive outbursts, fine intention tremor, pes cavus, and abnormalities of the toes. This syndrome was first described by Cazebas et al., in a family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
167
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(176 citation statements)
references
References 28 publications
(25 reference statements)
5
167
0
3
Order By: Relevance
“…To date, more than 80 genes have been implicated in XLMR, many more remain to be identified. The contribution of novel and high-throughput technologies is also making a mark on XLMR and MR gene discovery in general, for example, screening for submicroscopic rearrangements by array-comparative genome hybridization (array-CGH) characterized several genes with increased dosage associated with XLMR; [4][5][6] systematic re-sequencing of X-chromosome exon content [7][8][9] or brain-expressed genes has led to characterization of new XLMR genes acting in different signaling pathways, such as transcription regulation, postsynaptic neuronal signaling and complexes, regulation of cell cycle and ubiquitin pathway. 3,[10][11][12] Recently, the UPF3B gene (MIM 300298) encoding a member of the nonsense-mediated mRNA decay (NMD) complex has been found mutated in specific and nonspecific forms of XLMR in four families.…”
Section: X-linked Mr (Xlmr)mentioning
confidence: 99%
“…To date, more than 80 genes have been implicated in XLMR, many more remain to be identified. The contribution of novel and high-throughput technologies is also making a mark on XLMR and MR gene discovery in general, for example, screening for submicroscopic rearrangements by array-comparative genome hybridization (array-CGH) characterized several genes with increased dosage associated with XLMR; [4][5][6] systematic re-sequencing of X-chromosome exon content [7][8][9] or brain-expressed genes has led to characterization of new XLMR genes acting in different signaling pathways, such as transcription regulation, postsynaptic neuronal signaling and complexes, regulation of cell cycle and ubiquitin pathway. 3,[10][11][12] Recently, the UPF3B gene (MIM 300298) encoding a member of the nonsense-mediated mRNA decay (NMD) complex has been found mutated in specific and nonspecific forms of XLMR in four families.…”
Section: X-linked Mr (Xlmr)mentioning
confidence: 99%
“…Of the known genetic lesions, the X-chromosome harbors over 100 MR genes, far more than those found on autosomes. Recently, multiple mutations of the human CUL4B ubiquitin ligase gene (Xq24) were identified as being causally associated with X-linked MR (XLMR) [2][3][4][5]. CUL4B-deficient patients display clinical symptoms that include growth retardation, macrocephaly, hypogonadism, obesity, and ataxia [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…While CUL4B compensates for the loss of CUL4A [12], CUL4A expression, which is unaffected by CUL4B mutations [16], is apparently unable to rescue the neuronal and developmental deficiencies found in CUL4B patients with XLMR. Notably, the loss of CUL4B function is not lethal in humans [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…To date, mutations in about 100 genes have been identified in X-linked MR (XLMR), much more than those found on autosomes [9]. In 2007, two independent groups reported that mutations of CUL4B (Xq24) ubiquitin ligase gene are associated with XLMR [10,11]. CUL4B-deficient patients display a syndrome of delayed puberty, moderate short stature, hypogonadism, relative macrocephaly, central obesity, fine intention tremor, brachydactyly, and large tongue [10,11].…”
mentioning
confidence: 99%
“…In 2007, two independent groups reported that mutations of CUL4B (Xq24) ubiquitin ligase gene are associated with XLMR [10,11]. CUL4B-deficient patients display a syndrome of delayed puberty, moderate short stature, hypogonadism, relative macrocephaly, central obesity, fine intention tremor, brachydactyly, and large tongue [10,11]. Similarly, the neuronal and developmental deficiencies found in XLMR patients with CUL4B mutations are not compensated by CUL4A.…”
mentioning
confidence: 99%